PERANAN GAYA KEPEMIMPINAN DAN LATAR BELAKANG PENDIDIKAN DALAM MENINGKATKAN KINERJA KARYAWAN PT. INFOMEDIA SOLUSI HUMANIKA - Heni Cahya Ramdani; Femi Handayani; Islamiyah , (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
The purpose of this study to determine the roles of leadership and educational background in enhancing employee???s performance. ??The sample was 50 employees of PT. Infomedia Solusi Humanika. The method used in this research was descriptive quantitative and the analysis can be concluded that the leadership style has given positive and significant impact on employee???s performance but education background has not given positive impact. ??Both, the leadership style and educational background showed significantly influence to the performance of PT. Infomedia Solusi Humanika???employees.